2016
DOI: 10.1074/jbc.m116.717736
|View full text |Cite|
|
Sign up to set email alerts
|

Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Single Domain Antibodies Are Potent Inhibitors of Low Density Lipoprotein Receptor Degradation

Abstract: Single domain antibodies (sdAbs) correspond to the antigenbinding domains of camelid antibodies. They have the same antigen-binding properties and specificity as monoclonal antibodies (mAbs) but are easier and cheaper to produce. We report here the development of sdAbs targeting human PCSK9 (proprotein convertase subtilisin/kexin type 9) as an alternative to anti-PCSK9 mAbs. After immunizing a llama with human PCSK9, we selected four sdAbs that bind PCSK9 with a high affinity and produced them as fusion protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…To further verify the effect of the B11-Fc on lowering serum lipids in vivo, the hPCSK9 transgenic (Tg+) rat model was produced and induced by a high-fat diet. Before the formal experiment, we did a pre-experiment to probe an optimal dosage (20 mg/kg) according to the previous study [33]. In the formal experiment, the dual injections were on day 0 and day 7.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…To further verify the effect of the B11-Fc on lowering serum lipids in vivo, the hPCSK9 transgenic (Tg+) rat model was produced and induced by a high-fat diet. Before the formal experiment, we did a pre-experiment to probe an optimal dosage (20 mg/kg) according to the previous study [33]. In the formal experiment, the dual injections were on day 0 and day 7.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Our data revealed that the C-terminal Cys-His-rich domain (CHRD) of PCSK9, which contains three repeat structures called M1, M2, and M3 (Cunningham et al, 2007), is needed for the PCSK9-induced degradation of the PCSK9-LDLR complex (Nassoury et al, 2007), including the repeat domain M2 (Saavedra et al, 2012), which has 14 His (Cunningham et al, 2007) and a number of natural mutations associated with it . This critical importance of the CHRD in regulating the ability of PCSK9 to induce the degradation of the LDLR was confirmed in two independent studies (Zhang et al, 2008;Poirier et al, 2016) and was shown to be inhibited by mAbs (Ni et al, 2010;Schiele et al, 2014) or singledomain antibodies that target the CHRD, without inhibiting the PCSK9-LDLR complex formation (Weider et al, 2016).…”
Section: Cellular Studies: Mechanism Of Action Of Pcsk9mentioning
confidence: 70%
“…The structure of CHRD is organized in three Cys/His‐rich modules, termed M1, M2 and M3 53, 54. PCSK9 is synthesized as a zymogen and, in the ER, it undergoes autocatalytic cleavage, the latter process being required for PCSK9 maturation and secretion 55.…”
Section: Pcsk9 and Lipoprotein Receptorsmentioning
confidence: 99%
“…PCSK9 is a 692-amino acid secreted glycoprotein that consists of a signal sequence followed by a prodomain, a catalytic domain and a cysteine-and histidine-rich C-terminal domain (CHRD). The structure of CHRD is organized in three Cys/His-rich modules, termed M1, M2 and M3 [53,54]. PCSK9 is synthesized as a zymogen and, in the ER, it undergoes autocatalytic cleavage, the latter process being required for PCSK9 maturation and secretion [55].…”
Section: Pcsk9 and Lipoprotein Receptorsmentioning
confidence: 99%